Accuracy Analysis of WP, AHP-WP, Entropy-Topsis Methods in Determining Majors - Saiful Bahri; Maria Ulfah Siregar (Jurnal Nasional Pendidikan Teknik Informatika : JANAPATI, 2023)
Determination of majors at SMK AR Rahma is still manual and Excel is only used to find average scores. On the other hand, the number of students is around 140 students, so the majors can cause inaccuracies. In this study, the accuracy of the WP, AHP-WP, and ENTROPY-TOPSIS methods was analyzed in determining the majors of SMK AR Rahma’s students. So that it will be known which method is more accurate in producing student majors. In the process of student majors, data are needed in the form of report cards, academic test scores, majors test scores and health scores. The result is that the majors produced by the AHP-WP method are more accurate than the majors produced by the other two methods, respectively by 70.71%, 64.29%, and 62.86%.